(untitled) (Ameghiniana, 2013)
ABSTRACT: REVISION OF GENUS GOEPPERTELLA OISHI ET YAMASITA EMEND. (GOEPPERTELLOIDEAE- DIPTERIDACEA). In this paper the genus Goeppertella Oishi et Yamasita emend. is revised, based on the analysis of the morphology of eight species: G. diazii n. sp.; G. frenguelliana (Cazaubon) Stipanic et Menéndez; G. herbstií n. sp.; G. macrolaba Herbst; G. memoria-watabei Oishi et Huzioka; G. microloba (Schenk) Oishi et Yamasita; G. neuqueniana Herbst; G. varida Oishi et Huzioka. This paper includes a key for species, determination, synonymy lists, types (Iectotypes are selected for G. memoria-watabei Oishi et Huzíoka, G. microloba (Schenk) Oishi et Yamasita; and G. varida (Oishi et Huzíoka ) , some comments on special features, and the geographic and stratigraphic distribution for each species. The most important conclusions are: - The occurrence of the subsidiary elemens is a very significant taxonomic character. - Goeppertella is a good stratigraphic indicator, essentially for the Liassic times